Enterobacteriaceae kot povzročiteljice okužb s hrano v Sloveniji - Sodec, Barbara (Zdravstveno varstvo, 2006)
Foodborne diseases have spread worldwide and are frequent in Slovenia too. They are caused by enterobacteria Salmonella spp., Shigella spp., Yersinia enterocolitica and Esherichia coli ,common causative agents of enterocolitis in humans. Ofall enterocolitis cases reported in Slovenia between 1994 and 2002,10 % were caused by enterobacteria. Salmonellosis is the most commonly recorded type of food poisoning caused by enterobacteria. Salmonella enteritidis and Salmonella typhimurium are two frequently isolated pathogens. The rate of Salmonella infections increases in summer time, in all age groups.Typhoid fever and shigellosis occur rarely, and mostly affect individuals returning from developing countries. One case of typhoid fever anda few cases of shigellosis have been reported in recent years. Most cases of shigellosis are caused by Shigella sonnei and Shigella flexneri. Yersinia enterocolitica and enterohaemorrhagic E.coli 0157: H7 infections are rare in Slovenia.
Keywords: enterobakterije; Epidemiology; Escherichia Coli; Food Poisoning; hrana; Hrana, zastrupitev; infekcije; Microbiology; mikrobiologija; Salmonella Food Poisoning; Salmonelska zastrupitev hrane; Shigella Dysenteriae; Slovenia; Slovenija; Yersinia Enterocolitica; živila